Pendampingan pembelajaran IPA berbasis proyek dalam penguatan konsep sains siswa madrasah tsanawiyah - Ummi Kalsum; Nurul Fauziah; Tri Yuliawan; Desti Desti; Iffa Ichwani Putri; Ermawati S (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service activity aimed to assist teachers and students at a Madrasah Tsanawiyah in implementing project-based science learning to strengthen students' conceptual understanding of science. The partners' problems included teacher-centered instruction, limited application of innovative learning models, the unavailability of a science laboratory, and low student engagement in building meaningful comprehension of scientific concepts. The activity was conducted through five stages: needs analysis, teacher training, mentoring, learning implementation, and evaluation. The participants consisted of three teachers and 32 eighth-grade students. Data were collected using questionnaires, observations, tests, and documentation. The results showed an improvement in teachers' competence in designing and implementing project-based science learning, with an average pretest score of 64.6% increasing to 90% in the posttest. Students' conceptual mastery also improved, with an average pretest score of 53.8 rising to 82.5 in the posttest. Student responses to the learning process were highly positive, with a response rate of 88%. The outputs of this activity included project-based science learning kits and a scientific article on community service. In conclusion, this activity made a positive contribution to improving the quality of science learning at the Madrasah Tsanawiyah.